British Association of Dermatologists guidelines for the management of people with chronic urticaria 2021. (27th January 2022) - Sabroe, R.A.; Lawlor, F.; Grattan, C.E.H.; Ardern‐Jones, M.R.; Bewley, A.; Campbell, L.; Flohr, C.; Leslie, T.A.; Marsland, A.M.; Ogg, G.; Sewell, W.A.C.; Hashme, M.; et al.
Abstract : Plain language summary available online